1995
DOI: 10.1159/000154266
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 6p Microsatellite Polymorphisms in African-Americans

Abstract: Allele frequency distributions were determined for seven microsatellite DNA markers spanning the short arm of chromosome 6 in a population of African-Americans. A total of 196 chromosomes were analyzed. African-Americans differed from reported studies on Caucasians in the number of alleles, allele frequency and predominating alleles. These differences resulted in higher heterozygosity and polymorphic information content for these loci in the African-American population than in Caucasians. Each marker appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The heterozygosity level for TNFa was particularly high (0.85), and greater than 0.70 for D6S105 and D6S265 loci (see table 2). Nevertheless, Maliarik, Kost, Harrington et al (1995), characterizing several microsatellites located on chromosome 6 in a sample of Afro-Americans, found a heterozygosity value for D6S105 even higher (87%) than those reported for European populations. Table 3 includes results of the two tests for Hardy±Weinberg equilibrium.…”
Section: Resultsmentioning
confidence: 61%
“…The heterozygosity level for TNFa was particularly high (0.85), and greater than 0.70 for D6S105 and D6S265 loci (see table 2). Nevertheless, Maliarik, Kost, Harrington et al (1995), characterizing several microsatellites located on chromosome 6 in a sample of Afro-Americans, found a heterozygosity value for D6S105 even higher (87%) than those reported for European populations. Table 3 includes results of the two tests for Hardy±Weinberg equilibrium.…”
Section: Resultsmentioning
confidence: 61%
“…Modern day African Americans are a mixture of two genetically distinct populations, West African and European, and in the United States tend to have greater allelic diversity than Caucasians [8,9]. Studies of Y chromosome haplotypes estimate that part of the African population migrated to Eurasia between 40 and 50 thousand years ago [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous MR studies using UK Biobank have found higher BMI caused reduced socioeconomic position (higher deprivation, lower income, less years in education, lower odds of attaining a degree and lower odds of skilled employment), but did not find BMI causal on odds of employment [ 24 , 47 ]. A randomised control trial used financial reward to create differences in weight loss in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially be explained by reduced capacity to perform the work of caring for home or family. Alternatively, higher BMI in women has been found to be causal on lower probability of cohabiting with a partner [ 24 ], which in turn may associate with increased caring for home or family.…”
Section: Discussionmentioning
confidence: 99%